Teacher Professional Development in a Brazilian Context: Navigating Critical Literacies - Karla Ferreira da Costa (Papéis: Revista do Programa de Pós-Graduação em Estudos de Linguagens - UFMS, 2020)
This article explores the findings of an investigation about a teacher professional development course for elementary school teachers of English as an additional language (EAL), from public schools in Campo Grande, Mato Grosso do Sul, Brazil. This qualitative-interpretative teacher research is grounded in ethnographic and auto-ethnographic views and supported by theories of digital and multiliteracies (COPE & KALANTZIS, 2000, 2013; KALANTZIS & COPE, 2008; GEE, 2000), critical literacies (CERVETTI, PARDALLES, & DAMICO, 2001), and critical literacies pedagogies for bilingual contexts (MONTE MÓR, 2010, 2011, 2013; JORDÃO, 2013; MENEZES DE SOUZA, 2011). The research design aimed at promoting a shift in the views of the teacher research in a teacher education course. Collaborative teacher education work considers the co-responsibility and agency of the teacher-collaborator, in a globalized world characterized by the ephemerality and the velocity of choices posed by connectivity. Research data point to the relevance of continuous education that considers rethinking hegemonic and acritical education. There is a call to question acritical education that does not lead to inquiry or awareness-raising about how power relations influence and define teachers’ theoretical frames and practices. The possibilities for continuous education emerge in practical contexts when experiencing encounters and mismatches of practices and thoughts about what it means to teach and learn the English language as an additional language for the youth. This study aims to promote more contextualized, informed and critical reflections and practices while building collaborative relationships. These findings emphasize the importance of further investigating teacher education programs that consider the challenges and possibilities of a contemporary, connected, complex, and globalized world.